Behavior of high strength concrete with raw rice husk exposed to high temperature effect - Ucarkosar, B.; Yuzer, N.; Kabay, N. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2013)
The physical and mechanical properties of concrete change when concrete is exposed to high temperatures. As a result of these changes, concrete may exhibit damages, such as cracks and spalling. These damages are crucial, especially in High Strength Concretes (HSCs) due to the lower pore ratios in high strength concrete. In this study, Raw Rice Husk (RRH) and Polypropylene (PP) fibers were incorporated in concrete at 0.5-3% and 0.2-0.5% by weight of cement respectively and HSCs were produced. Concrete specimens were exposed to elevated temperatures of 20 (control) and 300 degrees C. Before and after this exposure, compressive and splitting tensile strength was determined. The pore structure of the concretes was characterized by determining ultrasonic pulse velocity. In addition, during the high temperature effect, the amount of the released harmful gases (CO, CO2) and oxygen was measured by a gas detector.
Keywords: Engineering; Environmental Sciences & Ecology; Materials Science